(untitled) (South Asian Journal of Agriculture, 2023)
Participation in government extension programs can help women farmers to achieve their livelihood aspirations. The study aimed to determine the achievement of women farmers’ livelihood aspirations, find its relationships with their selected characteristics, and identify the problems they faced in achieving livelihood aspirations and their potential solutions. Data were collected from 115 randomly selected respondents out of the population of 1148 from Phulbari Upazila of Dinajpur district using a pre-tested interview schedule from 15 February to 25 March 2019. A four-point rating scale measured the achievement of livelihood aspirations of the women farmers along with 30 activities covering five dimensions. The mean achievement of livelihood aspirations score was 43.74, with a standard deviation of 10.76. The achievement of livelihood aspirations was maximum for household food security and minimum for access to market opportunity. The majority of the women farmers (80.9%) belong to the medium status of livelihood aspirations, while only 10.4 % and 8.7% achieved low and high livelihood aspirations, respectively. Six out of eleven selected characteristics of the women farmers, such as educational qualification, farm size, organizational participation, use of information sources, agricultural knowledge, and attitude towards agricultural activities, showed significant positive relationships with their achievement of livelihood aspirations. The most reported problem faced by women farmers in achieving livelihood aspirations through agricultural activities is the “lack of quality seeds and seedlings”. Similarly, their top-ranked suggestion was to assure the quality and availability of seeds and seedlings as and when required at a reasonable price from government organizations. The agricultural extension programs should be designed with a gender-inclusive approach and take into account the specific needs and problems faced by women farmers to achieve their livelihood aspirations. South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 39-51